Drivers of Environmental and Social Entrepreneurial Intentions Among University Students: A Role of Sustainable Entrepreneurship Education and Theory of Planned Behavior Model - Aeni, Ida Nur; Widiatami, Anna Kania; Widhiastuti, Ratieh; Ridho, Muhammad Miftahur (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: Sustainable oriented entrepreneurial intention is an intention to become a sustainable entrepreneur, while sustainable oriented entrepreneurship is an entrepreneurial activity that not only pays attention to economic aspects, but also pays attention to social and environmental aspects.Purpose: The purpose of this study is to integrate the role of sustainable entrepreneurship education and the Theory of Planned Behavior model to investigate the drivers of sustainable entrepreneurial intention (environmental and social oriented) among undergraduate university students. Specifically, this paper aims to analyze the effect of sustainable entrepreneurship education, dimensions of the theory of planned behavior, and gender on sustainable entrepreneurial intentions. Design/methodology/approach: Data was gathered with the help of a structured questionnaire from 184 students of a university in Indonesia. SmartPLS was used to test the proposed structural model. Findings/Result: The findings revealed that sustainable entrepreneurship education significantly influences sustainable entrepreneurial intention. Sustainable entrepreneurial intention is significantly driven by subjective norms and perceived behavioral control. However, attitude and gender have a nonsignificant direct influence on sustainable entrepreneurial intentions. This study contributes toward an understanding of the sustainable entrepreneurial intention of university students.Conclusion: This research is that sustainable entrepreneurship education, subjective norms and perceived behavioral control have a role to drive sustainable oriented entrepreneurial intentions.Originality/value (State of the art): This study contributes toward an understanding of the sustainable entrepreneurial intention of university students. This study proposes integration and extension (by adding sustainable entrepreneurship education) and planned behavior theory to engage in sustainable entrepreneurship intentions. Keywords: environmental entrepreneurship, social entrepreneurship, sustainable entrepreneurship education, sustainable entrepreneurial intentions, theory of planned behavior